The structural relationship on sport values and continuous participation intention of the dance for all participants based on the 4 experience economy theory - Jeoung-hak Lee; Sun-young Lim (Korea Institute of Sport Science, 2020)
Purpose The purpose of this study was to examine the structural relationship between the sport values and continuous participation intention of the dance for all participants based on the 4 experience economy theory. Methods Frequency analysis, correlation analysis, confirmatory factor analysis and structural equation modeling using SPSS 21.0 and AMOS 18.0 were conducted to analyze the survey materials. Results First, the entertainment experience was a significant effect on all factors of sports value. Second, educational experience was a significant effect on all factors except sports entertainment value. Third, escapist experiences have a significant effect on all factors except physical value. Fourth, aesthetic experience has a significant effect on all factors of sports value. Fifth, social value and entertainment value was a significant influence on the continuous participation intention. Sixth, entertainment experience and aesthetic experience was a significant influence on the continuous participation intention. Conclusions Through these study results, it was confirmed that 4 experience, sport values and continuous participation intention of dance for all participants had a significant influence on each other.